APPLYING ENGAGING RESPONSE STRATEGY TO PROMOTE LITERARY APPRECIATION - Herlina Herlina; Santoso Santoso (Esteem Journal of English Education Study Programme, 2022)
This paper reviews about the studentsâ€™ response in literary appreciation of literature class.Â  The problem of this study was â€œIs the engaging response strategy able to promote literary appreciation of the fifth semester students of English Education Study Program of Faculty of Teachers Training and Education Â Â University of PGRI Palembang?â€ Â The objective of this study was to know or to identify the ability of the fifth semester students of English Education Study Program of Faculty of Teachers Training and Education University of PGRI Palembang in applying engaging response strategy to promote literary appreciation and, to identify the development of studentsâ€™ literary appreciation. The method used in this study was pre-experimental.Â  Â Â From the calculation of t-test, it was found out that the value of t-obtained was 4.2. It is higher than t table (1.687). It means that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. From the calculation, it was found out that there was a significant difference between the students who were taught by using engaging response strategy.